Republic of Lithuania : Staff Report for the 2001 Article IV Consultation and First Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2002)
This paper examines the Republic of Lithuania's 2001 Article IV Consultation and First Review Under the Stand-By Arrangement. The macroeconomic objectives for 2001 are expected to be largely attained and all end-September performance criteria and structural benchmarks were met. The authorities' priority is to stabilize revenue while creating a tax system consistent with European Union (EU) requirements. Underpinned by the fiscal adjustment, the currency board arrangement continued to anchor macroeconomic policies. The authorities remain committed to their ambitious structural reform agenda, which is driven in part by requirements of EU accession.